THE EFFECT OF ARTICULATE STORYLINE-BASED INTERACTIVE LEARNING MEDIA ON THE CHEMISTRY CLASS XI STUDENTS LEARNING OUTCOMES - Mudrikah; Raehanah; Taufik, Lukman (UIN Mataram, 2023)
The aim of this research is to determine whether there is an influence of articulate storyline-based interactive learning media on students' cognitive learning outcomes and affective learning outcomes in class XI chemistry learning. This research uses a quasi-experimental quantitative approach and a non-equivalent control group research design. The population of this study was all class XI IPA. The technique used for sampling was saturated sampling, class XI IPA I with a total of 36 students as the control class and class XI IPA II with a total of 41 students as the experimental class. Data collection uses multiple choice questions for cognitive learning outcomes and questionnaires for affective learning outcomes. Hypothesis testing uses the non-parametric Mann-Whitney test for univariate tests and Kruskal Wallis for multivariate tests. Based on the results of the hypothesis test, the following conclusions were obtained: 1) There is an influence of articulate storyline-based interactive learning media on students' cognitive learning outcomes in Class XI chemistry learning on a univariate basis, with a value of Sig. 0.002<0.05. 2) There is an influence of articulate storyline-based interactive learning media on students' affective learning outcomes in Class XI chemistry learning univariately, with a value of Sig. 0.000<0.05. 3) There is an influence of articulate storyline-based interactive learning media on students' cognitive learning outcomes and affective learning outcomes in Class XI chemistry learning in a multivariate manner, with a value of Sig. 0.000<0.05.